Retinoic Acid in the Immune System - Pino-Lagos, Karina (2008)
On occasion, emerging scientific fields intersect and great discoveries result. In the last decade, the discovery of regulatory T cells (T(reg)) in immunity has revolutionized our understanding of how the immune system is controlled. Intersecting the rapidly emerging field of T(reg) function, has been the discovery that retinoic acid (RA) controls both the homing and differentiation of T(reg). Instantly, the wealth and breadth of knowledge of the molecular basis for RA action, its receptors, and how it controls cellular differentiation can and will be exploited to understand its profound effects on T(reg). Historically, vitamin A deprivation and repletion and RA agonists have been shown to profoundly affect immunity. Now these findings can be interpreted in light of the revelations that RA controls leukocyte homing and T(reg) function.